Design of Inventory Monitoring Information System of Office Equipment and Supplies at BAZNAS City of Bandung Based on Macro Excel (VBA) - Okta Bella Yuan Lisyafa; Abdul Malik Sayuti (Ebiz Prima Nusa, 2024)
BAZNAS, the National Amil Zakat Agency, is the official institution overseeing zakat management at the national level. In Bandung City, BAZNAS runs programs such as Healthy Bandung, Smart Bandung, Taqwa Bandung, and Caring Bandung, contributing to the city's prosperity. To streamline office operations, related institutions must conduct inventory activities for office equipment and supplies. However, BAZNAS Bandung City currently employs a manual inventory management system, involving paper-based recording, recapitulation, and individual input into Excel sheets, leading to inefficiency, security concerns, and data loss risks. Recognizing the need for improvement, a new information system has been designed using Microsoft Excel, Macros, and Visual Basic Applications. The design includes Data Flow Diagrams and Entity Relationship Data to enhance the management and monitoring of inventory data, ensuring data integrity and structured inventory activities. Project evaluations, following the End User Computing Satisfaction (EUCS) principle, show that the system meets institutional needs and is user-friendly. Users are provided with a manual book during testing to enhance system understanding. While the trial results are positive, constructive feedback suggests the need for further feature enhancement to ensure smoother system operation and greater overall benefits. This information system aims to speed up and simplify inventory data management, bringing efficiency to BAZNAS Bandung City's operations.